Modern state of the undeveloped near-surface disposal of special radioactive wastes at the epicenter of the peaceful underground nuclear explosion «Crystal» (Yakutia): evidence from electrical resistivity tomography, land geomagnetic survey and water runoff study - Svetlana Yu. Artamonova; Aleksandr N. Shein (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. Risks of the radionuclides entering the human environment. Aim. To assess the current geoecological state of the undeveloped near-surface disposal of special radioactive wastes in the form of the block-rubble artificial cover at the epicenter of the peaceful underground nuclear explosion "Crystal". Object. Due to the explosion "Crystal", carried out in 1974 in the frozen rocks at the depth 98 m, an upthrust dome with a collapsed central part was produced at the epicenter. The central explosion area became the site of special radioactive wastes emplacement. A high content of radionuclides determined in epicenter soils exceeds the minimum activity values for solid waste. To cryogenic immobilization of radionuclides in epicenter soils and to prevent the radionuclides exit from the central explosion area, the head of the emplacement hole and the dome-shaped mound were buried under the block-rubble stone material (limestone and dolomite fragments) in 1992, and the artificial cover topped up in 2006. An ice-soil layer 0,6 m thick was frozen in it in 2006. Methods. Electrical resistivity tomography, land geomagnetic survey, radiometric measurements, liquid scintillation spectrometry, beta-radiometry and alpha-spectrometry with preliminary radiochemical preparation of countable samples. Results. The block-rubble artificial cover is not frozen and waterlogged. Snowmelt and rain waters seep through the cover. There is probably free air convection in the cover, which leads to the condensation of atmospheric moisture and then accumulation of water in it. Nevertheless, nowadays the migration of radionuclides with water from under the block-rubble artificial cover is characterized as low-intensity: the activity (Bq/dm3) of 3H is only 4–12, 90Sr – 0.004–0.4, 239,240Pu and 238Pu isotopes were not detected (<0.000001 Bq/dm3). According to these indicator parameters, there is currently no need in additional measures to strengthen or modify the block-rubble artificial cover.